The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/jmrs.25
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of exposure index (EI) values from plain radiographs reveals important considerations for quality improvement

Abstract: IntroductionFollowing X-ray exposure, radiographers receive immediate feedback on detector exposure in the form of the exposure index (EI).PurposeTo identify whether radiographers are meeting manufacturer-recommended EI (MREI) ranges for routine chest, abdomen and pelvis X-ray examinations under a variety of conditions and to examine factors affecting the EI.MethodsData on 5000 adult X-ray examinations including the following variables were collected: examination parameters, EI values, patient gender, date of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Although this article is based on the imaging of paediatric patients, many of the suggestions therein are also relevant to the imaging of adults. For example Mothiram et al highlighted gender variation in terms of EI when imaging adults, with female patient radiographs recording significantly higher median EI values than males in a number of instances 22. Mothiram et al have indicated that data on patient size and body part thickness could have provided useful information relating to the EI gender variations demonstrated in their study, as men and women have variations in tissue distribution,22 this would appear to validate a back to basics approach in terms of imaging adults utilising DR.…”
Section: Common Themesmentioning
confidence: 99%
See 4 more Smart Citations
“…Although this article is based on the imaging of paediatric patients, many of the suggestions therein are also relevant to the imaging of adults. For example Mothiram et al highlighted gender variation in terms of EI when imaging adults, with female patient radiographs recording significantly higher median EI values than males in a number of instances 22. Mothiram et al have indicated that data on patient size and body part thickness could have provided useful information relating to the EI gender variations demonstrated in their study, as men and women have variations in tissue distribution,22 this would appear to validate a back to basics approach in terms of imaging adults utilising DR.…”
Section: Common Themesmentioning
confidence: 99%
“…It has been reported that EI variations between examinations taken within hours and out of hours can occur, with higher EIs being recorded in the latter situation 22,32. This may be linked to staffing levels and levels of staff experience,22 with radiographers reluctant to have to repeat an exposure during these busy shifts 22,32.…”
Section: Studies On Eimentioning
confidence: 99%
See 3 more Smart Citations